Privatising power cuts? : ownership and reform of state electricity boards in India - Ruet, Joel.; Academic Foundation (New Delhi, India); France (New Delhi : Published by Academic Foundation, in association with Centre de Sciences Humaines, 2005)
Shows how privatisation is a one-sided game that has no real takers as long as SEBs remain organisations in which all technical, accounting, financial parameters are at the least hazy. This book pinpoints to the misconception in the very concepts generally used to analyse the internal organisation, the functioning, and the nature of SEBs.
Includes bibliographical references (p. [321]-329) and index.
oif 08/08/16
Loan
Keywords: Electric utilities; Privatization